Male tree weta are attracted to cuticular scent cues but do not discriminate according to sex or among two closely related species. (17th August 2017) - Wehi, Priscilla M.; Monks, Adrian; Morgan‐Richards, Mary
Abstract: Recognition of conspecifics is an essential precursor of successful mating. Where related species coexist, species discrimination might be important, but because related species are similar, species signal recognition may actually be low. Chemical cues such as cuticular hydrocarbons (CHCs) are frequently used by insects to identify suitable sexual partners. We predicted that New Zealand tree weta ( Hemideina spp.), a genus of nocturnal ensiferan Orthoptera that live both allopatrically and sympatrically, use chemical signals from either frass or CHCs to find mates. In a series of six laboratory trials using both H. thoracica and H. crassidens, we found that male tree weta, but not female tree weta, occupied cavities primed with female cuticular cues more often than cavities without. However, males did not discriminate between chemical cues of male and female conspecifics, or between conspecifics and heterospecifics. In field trials, tree weta did not occupy artificial cavities primed with either female frass or female cuticular cues more often than unscented cavities. However, in both trials weta preferentially returned to cavities that had already been occupied earlier in the trials. A final field trial confirmed the presence of mixed species harems during the mating season in one region of sympatry. Our results suggest that selection on sex and species specific chemical cues that could be used to find conspecific mates is weak. Mixed species aggregations suggest that identification of conspecific mating cues has not evolved to be species specific. We infer that for male tree weta, the cost of mating with heterospecifics is likely less than not mating at all.